John Logue: Socialism and Abundance. Radical Socialism in the Welfare State. A Study of the Danish Socialist People’s Party. (Akademisk Forlag, 1982). 353 s. - Peter Noack, Johan (Historie/Jyske Samlinger, 1985)
-